Morphological analysis of the reproductive system and molecular identification by mitochondrial markers COI and 16S rRNA of Megalobulimus oblongus (Mollusca, Strophocheilidae) of Colombia - Jaramillo Roldán, Erika (2014)
In this work was done morphological and molecular analysis to 28 land snails of Megalobulimus oblongus, collected in different departments of Colombia, deposited in a reference collection. For morphological characterization, the animals were dissected in a stereomicroscope. The reproductive system and the shell were described. Measures were taken to structures of the reproductive system. Of the shell were described its shape, color, number of whorls and ornamentation and equally basic measures were taken using a digital caliper. For molecular analysis were used two mitochondrial markers, 16S rRNA and cytochrome C oxidase subunit I (COI). Only one haplotype was obtained for each marker, even for individuals of different and distant biogeographical regions. This study suggests that M. oblongus is in danger, therefore are urgent investigations about reproduction, population genetics and biogeography to clarify its situation in Colombia. It also demonstrates that the reference collections and tissue banks are sources of valuable information since they allow knowing aspects related with the species´ risk that serve as an input for the design of conservation actions.